Differences in testosterone and its precursors by sex of the offspring in meconium. Issue 167 (March 2017) - Frey, Alexander J.; Park, Bo Y.; Schriver, Emily R.; Feldman, Daniel R.; Parry, Samuel; Croen, Lisa A.; Fallin, Daniele M.; Hertz-Picciotto, Irva; Newschaffer, Craig J.; Snyder, Nathaniel W.
Highlights: Measurement of testosterone, DHEA and androstenedione in human meconium. Testosterone was more abundant in meconium from male newborns. Dehydroepiandrosterone was more abundant in meconium from female newborns. Abstract: Prenatal metabolism exerts profound effects on development. The first stool of the newborn, meconium, provides a window into the prenatal metabolic environment. The objective of this study was to examine the feasibility of meconium as a novel matrix to quantify prenatal steroid levels. We quantified parameters of analytical interest regarding the use of meconium, including sample stability. We hypothesized that meconium steroid content would differ by sex, prompting analysis of meconium to test effects of prenatal steroid metabolism. Meconium from 193 newborns enrolled in the Early Autism Risk Longitudinal Investigation (EARLI) study, including 107 males, and 86 females, were analyzed by isotope dilution-liquid chromatography-high resolution mass spectrometry (ID–LC–HRMS) while blinded to identity for testosterone (T), androstenedione (AD), and dehydroepiandrosterone (DHEA). Steroid levels were compared by sex, and investigations of potential trends resulting from sample storage or processing was conducted. The unconjugated steroid content of meconium in ng/g (mean, standard deviation) was for males: T (2.67, 8.99), AD (20.01, 28.12), DHEA (13.96, 23.57) and for females: T (0.82, 1.63), AD (22.32, 24.38), DHEA (21.06, 43.49). T was higher in meconium from males (p = 0.0333), and DHEA was higher in meconium from females (p = 0.0202). 6 female and 3 male T values were below the limit of detection. No extreme variability in hydration or trend in steroid levels by storage time was detected. Sexually dimorphic levels of hormones may reflect gestational differentiation, and future studies should consider meconium analysis.